A new species of Dactyloa from eastern Panama, with comments on other Dactyloa species present in the region - Batista, Abel; Vesely, Milan; Mebert, Konrad; Lotzkat, Sebastian; Köhler, Gunther (Zootaxa, 2015)
Giant anoles of the genus Dactyloa have been considered to be represented in eastern Panama by six species. In this contribution, we describe a seventh species that is restricted to the Majé, San Blas, Darién, and Piedras-Pacora mountain ranges. The new species resembles D. ibanezi, D. limon, and D. purpurescens in external morphology but differs from these species in dewlap coloration, dorsal color pattern, morphometrics, and scalation. The recognition of the new species is further supported by DNA barcoding (genetic distances >2.7% in 16S and >7.8% in COI between the new species and all other species of Dactyloa). We discuss the taxonomic identity of D. purpurescens, and, based on morphological evidence, we place D. chocorum in the synonymy of the former species. An identification key for all 11 Dactyloa species occurring in Panama is provided.
Keywords: velikost orgánu; Animal Distribution; Male; Organ Size; Ecosystem; fylogeneze; anatomické struktury zvířat; Phylogeny; Panama; molekulární sekvence - údaje; mužské pohlaví; rozšíření zvířat; Lizards; ještěři; Animals; ženské pohlaví; Body Size; zvířata; velikost těla; ekosystém; Molecular Sequence Data; Female; Animal Structures